Effectiveness Educational Media with Video Media on The Compliance Female Adolescents Consuming Blood Enhancement Tablets - Astuti, Dewi Rinda; Syukur, Nursari Abdul; Lathifah, Adilah Azmi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
According to the World Health Organization, adolescents are residents aged 10-19 years. Data from the Samarinda City Health Office in 2021 in the health screening of junior high school children in 18 health centers in Samarinda, from a total of 3,072 female adolescents with a risk of anemia of 3.48%. Adolescent girls' awareness of the importance of consuming TTD as an effort to prevent anemia is still low. The Strategic Plan of the Indonesian Ministry of Health for 2015-2019 targets the coverage of TTD provision for female adolescents in stages from 10% (2015) to 30% (2019). The advantages of video media include being more interesting, easier to understand, can also be self-study, directly achieve goals and display content details, and can compare two different scenes at once. The purpose of this study is how effective video education media is on the compliance of adolescent girls in consuming iron tablets. Experimental research type. This research design uses a pre-experimental study method with one group pretest-posttest design. The results of the significance p-value of 0.000 <0.05.  So it can be concluded that video education media is effective in increasing knowledge of adolescent girls' compliance in consuming iron tablets.